BLOOD LEAD LEVELS AS RISK FACTOR FOR PREECLAMPSIA IN ASIAN CONTINENT: A SYSTEMATIC REVIEW - Risha Meilinda Marpaung; Ema Hermawati (Universitas Pahlawan Tuanku Tambusai, 2023)
Preeclampsia is a hypertensive disorder in pregnancy which complicates around 2-8% of all pregnancies in the world. Based on estimates from the World Health Organization (WHO), the prevalence of preeclampsia in developing countries is seven times higher than in developed countries. Preeclampsia also causes death of pregnant women in Africa and Asia, around 9%. Increased serum lead levels of pregnant women are associated with an increased risk of preeclampsia. This systematic review study aims to review articles discussing whether blood lead levels are a risk factor for preeclampsia in Asian Continent. This research is a systematic review using PRISMA guidelines. Articles were obtained from several scientific databases, such as Pubmed, Google Scholar, ProQuest, Scopus, and Science Direct (published between 2015 and 2022), using relevant keywords including (